PENGARUH ELECTRONIC WORD OF MOUTH BEAUTY VLOGGER WARDAH ONE BRAND MAKEUP TUTORIAL FATYA BIYA TERHADAP MINAT BELI PRODUK WARDAH - Atika "; Suyanto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
Various types of videos but one that is often encountered is a video about beauty vlog which contains beauty things, appearance also beauty tips and tricks from a beauty vlogger. One of them is Fatya Biya, a beauty vlogger who has been active since 2015. The videos she uploads are related to beauty and appearance, tutorials, tips and tricks on makeup. One of her very popular video is Wardah One Brand Makeup Tutorial which leads to one of the top of the search on Youtube if you want to look for makeup tutorials using a brand called Wardah.The purpose of this research is to find out how much influence electronic word of mouth Wardah One Brand Makeup Tutorial Fatya Biya toward purchase intention Wardah product.This research was also conducted with an explanative quantitative method with non-probability sampling technique and using the Slovin formula which obtained a sample of 100 respondents. After deploying the questionnaires through Google form, the researchers analyzed the data using the SPSS for Windows application  version 25.Based on the results of a simple linear regression analysis, the results of the coefficient value in the study is Y = 9,703 + 0.406 X. The constant number (a) is 9,703 and the variable coefficient of electronic word of mouth beauty vlogger Wardah one brand makeup tutorial Fatya Biya is 0.406. Where, Ho is rejected and Ha is accepted with a significance level of 0.000. If the significance level is smaller than the significance level of 0.05, it can be concluded that there is an effect between Wardah's electronic word of mouth beauty vlogger one brand makeup tutorial Fatya Biya on the interest in buying Wardah products. The coefficient of determination or R square (R2) in this study is 48.2%, which shows the influence of electronic word of mouth beauty vlogger Wardah one brand makeup tutorial by Fatya Biya on buying interest in Wardah products is in the moderate category. Keywords: Electronic Word of Mouth, Beauty Vlogger, Purchase Intention, Wardah